2022
DOI: 10.1167/iovs.63.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Geniculate Nucleus Volume Determined on MRI Correlates With Corresponding Ganglion Cell Layer Loss in Acquired Human Postgeniculate Lesions

Abstract: Purpose To quantitatively assess lateral geniculate nucleus (LGN) volume loss in the presence of lesions in the postgeniculate pathway and its correlation with optical coherence tomography retinal parameters. Methods This was a case control study of patients recruited at the University Hospital Zurich, Switzerland. Nine patients who were suffering from lesions in the postgeniculate pathway acquired at least 3 months earlier participated. Retinal parameters were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 51 Conversely, training within the intact field locally stimulates circuits that are not directly affected by V1 damage-mediated TRD. 26 , 29 , 43 Although V1 areas of both hemispheres representing visual information along the vertical meridian are connected via callosal axonal projections, 60 notable due to the training locations of these participants, these interhemispheric connections do not appear to provide enough benefit to the anterior portion of the visual pathway to be observable at the level of the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 51 Conversely, training within the intact field locally stimulates circuits that are not directly affected by V1 damage-mediated TRD. 26 , 29 , 43 Although V1 areas of both hemispheres representing visual information along the vertical meridian are connected via callosal axonal projections, 60 notable due to the training locations of these participants, these interhemispheric connections do not appear to provide enough benefit to the anterior portion of the visual pathway to be observable at the level of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] In humans, structural magnetic resonance imaging (MRI) analyses have shown that the optic tract ipsilateral to occipital cortex damage is often reduced in size, 25,29,30,[32][33][34][35] as are the thicknesses of the ganglion cell and nerve fiber layers in corresponding regions of the retina in each eye. 24,[28][29][30][31][32]34,[36][37][38][39][40][41][42][43][44][45] Retinal ganglion cells (RGCs) are responsible for preprocessing and ferrying visual information to the rest of the visual system. As such, their loss or dysfunction could significantly threaten the potential to recover visual functions in participants with primary visual cortex (V1) damage.…”
mentioning
confidence: 99%
“…Atrophy of the LGN is a critical pathological indication for V1 lesions which can be quantified with non-invasive brain imaging (Simmen et al, 2022). Whereas volume reduction is clearly influenced by neuronal loss, these two aspects of degeneration can occur independently.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions in the primary visual cortex (V1) trigger degeneration and volume loss in the lateral geniculate nucleus (LGN), both in human and non-human primates (Atapour et al, 2017(Atapour et al, , 2021Cowey & Stoerig, 1989;Hendrickson et al, 2015;Simmen et al, 2022). The widespread degeneration involves projection neurons in the magno-(M), parvo (P), and koniocellular (K) neurons as well as corticogeniculate fibers (Atapour et al, 2017;Kinoshita et al, 2019;Wong-Riley, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this may increase the likelihood that these neurons are retained long-term in the residual visual circuitry, perhaps providing the neural substrates of training-induced recovery of visual functions seen deeper into the visual deficit 51 . Conversely, training within the intact field locally stimulates circuits that are not directly affected by V1 damage-mediated TRD 26,29,43 . Though V1 areas of both hemispheres representing visual information along the vertical meridian are connected via callosal axonal projections 60 , notable due to the training locations of these participants, these interhemispheric connections do not appear to provide enough benefit to anterior portion of the visual pathway to be observable at the level of the retina.…”
Section: Discussionmentioning
confidence: 99%